Communication optimization method of digital-analog hybrid simulation system based on min-cut partition - Li Yiyuan; Mu Qing; Xue Wei (Dianzi Jishu Yingyong)
Digital-analog hybrid simulation is essential for understanding the real power grid and supporting power grid security. Complex power network topology and hard real-time simulation put forward high requirements for computing performance. At present, digital-analog hybrid simulation mainly uses parallel computing technology to improve computing performance. With the development of processor and cluster technology, heterogeneous cluster systems have gradually become the primary construction method of high-performance computing systems. For the multi-level system architecture, the existing power grid division methods can not fully use the cluster computing power. Dealing with the high latency of cross-layer communication and the unequal number of available processor cores on each computing node due to heterogeneous acceleration equipment is the main challenge of the partitioning and mapping algorithm. Aiming at the electromagnetic transient simulation system ADPSS developed by China Electric Power Research Institute, this paper designs a two-stage integrated optimization algorithm of power grid division and process mapping, which achieves a better load balance and minimizing communication, and further reduces the calculation time of the electromagnetic transient simulation. The algorithm is based on the min-cut partition and effectively solves the optimal mapping of sub-networks of unequal sizes on heterogeneous cluster systems. The simulation test was realized on the real power grid in Northwest and East China, compared with the ADPSS default partition and mapping algorithm, the proposed algorithm achieves an average communication performance improvement of 40% and 50% and an average overall computing performance improvement of 10% and 12%.